2011
DOI: 10.5253/078.099.0208
|View full text |Cite
|
Sign up to set email alerts
|

Immature Survival and Age at First Breeding of Damara Terns: Conservation from a Non-Breeding Perspective

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Also, variation in estimated pre-breeding survival is partly introduced by the age at which chicks are ringed, which also varies in the different published studies. Chicks ringed closer to fledging provide a higher estimate of survival to recruitment than chicks ringed soon after hatching, indicating that substantial mortality occurs between hatching and fledging (Robinson 2010;Braby et al 2011). Our pre-breeding survival estimate (0.54) is much higher than the only other estimate obtained for a tern of the same genus-the Black Tern in Wisconsin, USA (\0.02 %; Shealer 2007).…”
Section: Pre-breeding Survivalmentioning
confidence: 58%
See 2 more Smart Citations
“…Also, variation in estimated pre-breeding survival is partly introduced by the age at which chicks are ringed, which also varies in the different published studies. Chicks ringed closer to fledging provide a higher estimate of survival to recruitment than chicks ringed soon after hatching, indicating that substantial mortality occurs between hatching and fledging (Robinson 2010;Braby et al 2011). Our pre-breeding survival estimate (0.54) is much higher than the only other estimate obtained for a tern of the same genus-the Black Tern in Wisconsin, USA (\0.02 %; Shealer 2007).…”
Section: Pre-breeding Survivalmentioning
confidence: 58%
“…Spendelow et al 2002;Lebreton et al 2003, Monticelli et al 2008b, Braby et al 2011Feare and Doherty 2011;Braby et al 2012). The data presented here are the first estimates of survival for this species.…”
Section: Adult Survivalmentioning
confidence: 73%
See 1 more Smart Citation
“…Nisbet and Cam 2002;Szostek and Becker 2012; other seabirds: e.g. Breton et al 2006;Braby et al 2011;Emmerson and Southwell 2011;Pardo et al 2013). This indicates that first-time breeders, irrespective of age, were not subject to lower survival through an elevated cost of reproduction, (at least not immediately, long-term costs might apply: e.g.…”
Section: Annual Survival Ratesmentioning
confidence: 98%
“…One incubating adult caught on 19 January 2010 was thought to be two years old; it exhibited three series of primary moult and had a brownish crown rather than the full black crown of the other breeding adults. The age at first breeding of Damara Terns was estimated to be 3-4 years (Braby et al 2011a), although one individual aged two years was found incubating in Namibia. Age at first breeding may be at two years in the closely related Little Tern Sternula albifrons, although it is normally later (Cramp 1983).…”
Section: Biology Of the Eastern Cape Damara Tern Populationmentioning
confidence: 99%